Electronic Mall of ORI Kemaman (e-OKEM) / Nur Nadiah Faqihah Mt Jais - Mt Jais, Nur Nadiah Faqihah (2018)
Today everyone has a desire to start up a new business as a purpose of their daily income. To start up a business, it is compulsory to register with Suruhanjaya Syarikat Malaysia (SSM). Basically, Small and Medium-sized Enterprises (SMEs) sell their product only from home, on the website, social media such as Facebook or attend any event held by FAMA. ORI Kemaman is selected to help the SMEs, however they do not have a proper platform for SMEs to conduct their businesses. They faced difficulty to track the sales as well as difficulty to recognize the SMEs product in the future. Hence, electronic mall (e-mail) was developed to assist ORI Kemaman in providing a platform to manage SMEs business process. Generally, e-mall consists of collection of e-shop. One or more companies selling a similar product to display at the e-catalogs. This platform will promote and advertise all the SMEs products from Kemaman district. The purposes to help the SMEs increase their sales revenue. ORI Kemaman was adapted Rapid Application Development (RAD) model which comprises of four phase life cycle, such as Requirement Planning, User Design, Construction, and Cutover. There are three experts and thirty respondents was evaluated the system regarding the functionality and the usability of the system. All the comment and suggestion will be used for future enhancement. A set of questionnaire were distributed to evaluate the system. The data was collected and the result shows that the majority of the respondents are satisfied with the efficiency of the system which is the highest mean 4.53 (SD=0.57). Conclusively, the majority of the respondents is satisfied with e-OKEM. For future work, it hoped will enhanced the flow of the current business process for the SMEs and the participants such as staff and entrepreneurs as well.